ISLAM AS POPULIST CURRENCY: The Indonesian Case of Religious Nationalism and the Quest for Power - Sofiandi, Sofiandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This article investigates the instrumentalization of Islam as a populist currency in Indonesia’s contemporary political landscape. Through a critical discourse analysis of the 2017 Jakarta gubernatorial election and the 2019 presidential campaign, the study examines how political and religious actors mobilize Islamic narratives, symbols, and emotional appeals to construct the moral superiority of “the people” and delegitimize their opponents. It argues that Islam functions not merely as a system of belief, but as symbolic capital—used strategically to moralize authority, forge collective identity, and exclude ideological and religious “others.” The findings reveal how religious populism in Indonesia has contributed to the erosion of pluralist values and the consolidation of exclusionary politics. The article offers a conceptual proposition of “Islam as populist currency” to understand this phenomenon, and reflects on its implications for democracy, tolerance, and civil society in the world’s largest Muslim-majority democracy.